PENGEMBANGAN MAJALAH BERBASIS KEARIFAN LOKAL TERINTEGRASI PROFIL PELAJAR PANCASILA PADA MATERI SUHU DAN KALOR UNTUK SEKOLAH DASAR - Silvya Damayanty; Riawan Yudi Purwoko; Nur Ngazizah (LPPM Universitas Cipta Mandiri, 2024)
This research aims to 1) produce a magazine product based on local wisdom integrated with Pancasila student profiles on temperature and heat material for elementary schools, 2) find out the feasibility of a magazine product based on local wisdom integrated with Pancasila student profiles on temperature and heat material for elementary schools. The type of research used is research and development (R&D), with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research subjects were class V students at SDN Kembangkuning for the 2022/2023 academic year. The data collection techniques and instruments used were observation, interviews, test sheets and questionnaires. The results of research and development in the form of product validity obtained an average score of 3.71 with a classification of